Political life after civil wars: Introducing the Civil War Successor Party dataset. (July 2021) - Daly, Sarah Zukerman
Around the world, following civil wars, rebel and government belligerents contest and win the founding postwar elections. Despite the prevalence of these elections and their importance in setting post-conflict environments on specific political trajectories, their outcomes have been understudied. Existing scholarship centers on the timing and institutions of the postwar elections, but not on their party and voter participants. This article introduces a dataset which traces the postwar political trajectories of civil war belligerents, identifies their successor parties, charts their electoral performance, and documents their decision to remilitarize or demilitarize. The Civil War Successor Party (CWSP) dataset covers all belligerents that have transitioned from civil conflict in the period 1970–2015. The article describes the contours of the dataset, reveals patterns of political life after wars, and outlines the potential uses of the dataset for future research. In particular, it suggests how the data may be leveraged by scholars and practitioners to understand dynamics of political behavior, patterns of governance and public goods provision, quality of democracy, and recurrence of low- and high-intensity war in the aftermath of mass violence.